Biological evaluation of gallic acid and quercetin derived from Ceriops tagal: insights from extensive in vitro and in silico studies. Issue 4 (4th March 2022) - Sachithanandam, V.; Parthiban, A.; Lalitha, P.; Muthukumaran, Jayaraman; Jain, Monika; Elumalai, Dhanasekar; Jayabal, Kamalraja; Sridhar, R.; Ramachandran, Purvaja; Ramachandran, Ramesh
Abstract: Gallic acid (PubChem CID: 370) and quercetin (PubChem CID: 5280343) are major phenolic compounds in many mangrove plants that have been related to health cure. In the present study, the active fractions namely gallic acid (1) and quercetin (2) were isolated from the methanolic extract of leaves of Ceriops tagal in a Tropical mangrove ecosystem of Andaman and Nicobar Island (ANI), India. The chemical structures were determined by spectroscopic analysis: Fourier-Transform Infrared spectroscopy (FT-IR), 1 H, 13 C Nuclear Magnetic Resonance (NMR) spectroscopy, and High-resolution mass spectrometry (HRMS). The anticancer activity of isolated compounds (1) and (2) were evaluated by in vitro assays against two human cancer cell lines namely, HeLa (Cervical) and MDA-MB231 (Breast) cancer cells revealed that IC50 values of gallic acid (HeLa: 4.179197 ± 0.45 µg/ml; MDA-MB231: 80.0427 ± 0.19 µg/ml at 24 h) and quercetin (HeLa: 99.914 ± 0.18 µg/ml; MDA-MB231: 18.288382 ± 0.12 µg/ml at 24 h), respectively. Antioxidant properties of gallic acid (1 ) and quercetin (2 ) are found to be IC50 value of 0.77 ± 0.41 µg/ml and 1.897 ± 0.81 µg/ml, respectively. Molecular docking results explained that gallic acid (1 ) and quercetin (2 ) showed estimated binding free energy ( ΔG ) of −5.4 and −6.9 kcal/mol towards drug target Bcl-B protein, respectively. The estimated inhibition constant ( Ki ) for these two molecules are 110 and 8.75 μM, respectively. The MD simulation additionally supported that quercetin molecule is significantly improved the structural stability of Bcl-B protein. The present study provides key insights about the importance of polyphenols, and thus leads to open the therapeutic route for anti-cancer drug discovery process. Communicated by Ramaswamy H. Sarma